Rhetorical Structure and Linguistic Features of Abstracts: A Comparative Study Of Local, National And International Journals In English Education Written by Indonesian Authors - Safnil Arsyad; Husnul Hakim; Hellen Astria (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
The abstract is an important part of a research article; it is a research summary that must be attached, presented together with the research article. Therefore, the quality of an abstract is explicitly significant. This article aims to determine the similarities and differences of the rhetorical moves and linguistic features of abstracts of local, national, and international journals by Indonesian authors in the field of English language teaching. The method used is descriptive quantitative and qualitative methods or mix-methods by analyzing the communicative objectives and linguistic features of the abstract parts of research articles. The results show that the majority of Ijal abstracts have five moves while the majority of Edu-Ling abstracts have only three moves. In general, active sentences are used more dominantly used than passive sentences in all moves of all three groups of abstracts, and present tense is far more frequently used in Ijal and Teflin abstracts but past tense is more frequently used in Edu-Ling abstracts while that-complement clause in Move-4 of Ijal abstracts is the most frequently used among the three groups of abstracts. It can also be concluded that Teflin article abstracts are more similar to those of Ijal articles than to Edu-Ling articles in all aspects. This is probably because Teflin authors are more experienced in writing journal articles than those of Edu-Ling articles.